A Drone-Based 0.7-4.7 GHz FMCW Radar System for High-Resolution Exploration of Subsurface Glacier Structures - Stelzig, Michael; Benedikter, Andreas; Kleinlein, Micha; Haberberger, Niklas; Krabbe, Lena; Lomakin, Konstantin; Braun, Matthias; Krieger, Gerhard; Vossiek, Martin (2023 IEEE International Radar Conference (RADAR), 2023)
A majority of the studies on subglacial structure mapping and imaging have relied on low-frequency ground penetrating radar (GPR) systems. In particular, mapping alpine glaciers using surface-based high-resolution radar sensors poses a considerable threat to the operators due to crevasses or avalanches; this can be avoided by deploying an unpiloted aerial vehicle (UAV)-based radar sensor. Herein, we present an ultrawideband (UWB) bistatic frequency-modulated continuous-wave (FMCW) GPR for operation on a UAV. By using a UAV equipped with ultrawideband and extremely lightweight additively manufactured horn antennas at a bandwidth of 4GHz between 0.7 GHz and 4.7 GHz we acquired ultra-high-resolution images of the upper firn layers of an alpine glacier. The acquired measurements at the Jungfraufirn, Switzerland illustrate the out-standing performance of the overall system and its applicability in glaciological research.<br
Keywords: Ground penetrating radar; Horn antennas; Radar; Bandwidth; Radar imaging; Radar antennas; Autonomous aerial vehicles; Unpiloted Aerial Vehicle; Frequency-Modulated Continuous-Wave Radar; Horn Antenna; Subsurface Imaging; Glacial Exploration; Ground Penetrating Radar

A Pseudo-Random Noise-Coded 1.35 GHz Sequential Sampling Impulse Radar System for Forefield Reconnaissance for Ice Exploration Melting Probes - Haberberger, Niklas; Stelzig, Michael; Krabbe, Lena; Hehn, Markus; Vossiek, Martin (2024 21st European Radar Conference (EuRAD), 2024)
Presented in this study is a sequential sampling impulse radar (SSIR) system with pseudo-random noise (PRN) coding designed for forefield reconnaissance for melting probes, enabling the subsurface exploration of icy moons, such as Europa and Enceladus. Characterized by simple hardware and a compact form factor, the developed multi-channel SSIR utilizes pseudo-random noise sequences to effectively enhance the signal-to-noise ratio (SNR). Demonstrating exceptional sensitivity and performance, a prototype system was tested on the Langenferner glacier in Ital

A Radar and Sonar-Based Hybrid Forefield Reconnaissance System for Melting Probes for Englacial Exploration - Stelzig, Michael; Haberberger, Niklas; Audehm, Jan; Becker, Fabian; Nghê, Chi Thanh; Ellinger, Enrico; Do, Mia; Krabbe, Lena; Heinen, Dirk; Zierke, Simon; Böck, Georg; Helbing, Klaus; et al. (IEEE Transactions on Geoscience and Remote Sensing, 2024)
The polar regions of Mars as well as the ice-covered moons such as Saturn’s Enceladus and Jupiter’s Europa have emerged as significant targets for ongoing and future space missions focused on investigating potentially habitable celestial bodies within our solar system. A key objective of these missions is to explore subglacial water reservoirs lying beneath the ice crusts of moons, such as Europa. The utilization of melting probes shows immense promise for achieving this goal. However, in addition to the capability to melt through the ice body, such a probe must also be able to identify the ice–water interface as well as obstacles in its path, such as cavities or meteoric rocks. To address these challenges, we present a forefield reconnaissance system (FRS) featuring a hybrid sensing approach that combines radar and sonar both integrated into the tip of a melting probe. Furthermore, the system includes an in situ permittivity sensor to ensure accurate radar range assignment and to gather scientific data about the ice body. The system has been integrated into a demonstrator melting probe and tested in a terrestrial analog scenario. Measurements at the Jungfraufirn in Switzerland confirm the potential of the developed system.<br
Keywords: Probes; Radar; Reservoirs; Sonar; Heating systems; Snow; Permittivity; Radar System; Solar System; Thermal Conductivity; Dielectric Constant; Autonomous Vehicles; Acoustic Signals; Inertial Measurement Unit; Vector Network Analyzer; Phase-locked Loop; Simultaneous Localization And Mapping; Planar Antenna; Gallium Nitride; Robot Operating System; Ground Penetrating Radar; Aluminum Nitride; Coaxial Line; German Aerospace Center; High Power Amplifier; Protection Circuit; Outer Conductor; Relative Permittivity Values; Acoustic Transducer; Extraterrestrial Life; Binary Phase Shift Keying; Stray Field; Echo Signal; Test Locations; Antenna Array; Radar Measurements; Equivalent Circuit

A Synthetic Aperture Imaging Concept for a Sequential Sampling Impulse Radar - Krabbe, Lena; Haberberger, Niklas; Stelzig, Michael; Hehn, Markus; Vossiek, Martin (German Microwave Conference (GeMiC), 2024)
Sequential sampling impulse radar, which is known for its low complexity and potential energy efficiency, has seen limited exploration of its imaging capabilities, particularly for synthetic aperture radar (SAR) focusing. This paper fills this gap by introducing a phase-based SAR imaging concept for a sequential sampling impulse radar without IQ-mixer. This work outlines a mathematical model for the received echo signal and processing steps to extract the phase information from the real-valued radar data. Experimental validation is performed in an outdoor scenario. The measurement results demonstrate successful phase-based SAR focusing, overcoming the limitations of amplitude-based reconstruction. The signal processing and imaging concept shown in this paper, combined with the used 1.35 GHz sequential sampling impulse radar systems, is intended for future use in glaciological research for the enhanced monitoring of glacier stratification, but it is also suitable for many other high-resolution ground penetrating radar (GPR) applications.<br
Keywords: synthetic aperture radar; sequential sampling impulse radar; switched oscillators; backprojection

A Tutorial on the Sequential Sampling Impulse Radar Concept and Selected Applications - Vossiek, Martin; Haberberger, Niklas; Krabbe, Lena; Hehn, Markus; Carlowitz, Christian; Stelzig, Michael (IEEE Journal of Microwaves, 2023)
The sequential sampling impulse radar is a radar concept that has been known for a very long time. Ultrawideband (UWB) radar systems have been realized based on this concept long before the popular phrases UWB and UWB radar were created. Its hardware simplicity, low cost, potentially high bandwidth and high range resolution, as well as the unsurpassed low power consumption of some of its variants have made it one of the most widely used radar concepts in industrial automation today. Despite its widespread use in practice, however, there are only few publications, textbooks and tutorials that describe this concept in detail and all its varieties and aspects. Especially, the correlation properties and the resulting signal-tonoise ratio (SNR), as well as the phase injection locking of pulsed oscillators, that is required for powerefficient options, have rarely been described in detail. This tutorial introduces the typical sequential sampling impulse radar concept step by step and presents the characteristics and pros and cons. As for the correlation properties and the SNR, the concepts are compared to those of standard coherent impulse radar systems and of frequency modulated continuous wave (FMCW) radar. In addition to the system theory, selected applications are presented to illustrate the attractiveness and elegance, but also the limits, of this interesting and important radar concept. The shown applications range from those in the main field of use of this type of radar, that is, industrial automation, to former and current radar concepts in the areas of automotive radar, ground penetrating radar (GPR), security scanners, and biomedical radar system
Keywords: Ground penetrating radar; Power demand; Costs; Radar measurements; Tutorials; Radar imaging; Radar tracking

A UAV-based Radar Sounder SAR System for the Imaging of Internal Snow and Firn Stratifications - Stelzig, Michael; Benedikter, Andreas; Krabbe, Lena; Schultz, Jakob; Haberberger, Niklas; Braun, Matthias; Krieger, Gerhard; Vossiek, Martin (Proceedings of the European Conference on Synthetic Aperture Radar, EUSAR, 2024)
Unpiloted aerial vehicle (UAV)-based synthetic aperture radars (SAR) offer great potential for use in the structural mapping of snow and firn structures, such as crevasses or stratifications within the subsurface of alpine glaciers. Especially advantageous is the possibility to conduct autonomous and wide-area measurements of a glacier without the risk of crevasse fall or avalanches for ground-penetrating radar (GPR) operators. We present an imaging approach for the mapping of snow and firn structures based on a UAV-borne GPR system, capable of precisely accommodating the refraction effects at the surface. Several common methods for estimating the refraction at the dielectric interface for a planar surface are presented, and their performance is evaluated. As the topography of an alpine glacier is rarely planar, an imaging approach for arbitrary surfaces is presented, which relies on the extraction of the surface from the raw radar B-scan. Measurements from a sand pit experiment confirm the applicability of the imaging approach before the algorithm is applied to measurements from the Jungfraufirn glacier, Switzerland, highlighting the great potential of UAV-based GPR for use in future glacial research.
CRIS-Team Scopus Importer:2024-05-31

Experimental Verification of a Digital Delay Transponder Used as an In-Ice Synthetic Aperture Radar Reference Target - Stelzig, Michael; Benedikter, Andreas; Horn, Ralf; Jaeger, Marc; Keller, Martin; Scheiber, Rolf; Haberberger, Niklas; Krabbe, Lena; Krieger, Gerhard; Vossiek, Martin (2023 53rd European Microwave Conference (EuMC), 2023)
Low-frequency radar systems offer great potential to support navigation systems of exploratory ice-penetrating probes for cryospheric applications. Due to the comparably small radar cross-section (RCS) of such probes, transponder-like functionalities are mandatory to realise an increased RCS for a reliable in-ice detection and localisation of these probes. To support such applications, a miniaturised monostatic digital delay transponder was developed and tested in a measurement scenario with an airborne synthetic aperture radar (SAR) sensor on an alpine glacier.<br
Keywords: Radar cross-sections; Prototypes; Tomography; Signal processing; Delays; Radar applications; Transponders; Pulse compression radar; radar cross-section (RCS); synthetic aperture radar (SAR); transponder

Instantaneous Ego-Motion Estimation Using a Coherent Radar Network - Hoffmann, Marcel; Krabbe, Lena; Schüßler, Christian; Gulden, Peter; Vossiek, Martin (2022 19th European Radar Conference (EuRAD), 2022)
This paper presents an approach to estimate the ego-motion of a vehicle equipped with a network of two or more coherently working bistatic or multistatic MIMO radars. The multi-perspective view of this setup allows for an immediate determination of the radar targets' relative velocity vector. The ego-motion is then derived from the inverted vectorial velocity of all static targets that can be obtained by clustering the velocity vectors. For this, it can be assumed that the majority of the detected targets are static, thus generating the largest cluster. The novel approach was tested with a setup consisting of two 77 GHz front-looking, long-range radars that only exhibit a narrow field of view with a small azimuth variation. The functionality of the proposed algorithm was evaluated and confirmed in a highway test driv
Keywords: motion estimation; Doppler radar; wireless sensor networks; automotive applications